Cellular bucket brigades on U-lines with discrete work stations - LIM, Yun Fong (Institutional Knowledge at Singapore Management University, 2014)
It is challenging to maximize and maintain productivity of a U-line with discrete stations under the impact of variability. This is because maximizing productivity requires assigning workers to suitable tasks and maintaining productivity requires sufficient flexibility in task assignment to absorb the impact of variability. To achieve this goal, we propose an operating protocol to coordinate workers on the U-line. Under the protocol the system can be configured such that its productivity is maximized. Workers are allowed to dynamically share work so that the system can effectively absorb the impact of variability. Analysis based on a deterministic model shows that the system always converges to a fixed point or a period-2 orbit. We identify a sufficient condition for the system to converge to the fixed point. Increasing the number of stations improves productivity only under certain circumstances. The improvement is most significant when the number of stations in each stage increases from one to two, but further dividing the U-line into more stations has diminishing return. Simulations based on random work velocities suggest that our approach significantly outperforms an optimized, static work-allocation policy if variability in velocity is large.